Faktor Perilaku Investor Millenial Dalam Transaksi Saham di Pasar Modal - Hartini, Kustin; Asnaini, Asnaini (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to determine the factors that shape the behavior of millennial investors in stock transactions in the Capital Market. This type of research is quantitative using an exploratory quantitative approach. The data analysis technique in this study used exploratory factor analysis using the JASP (Jeffrey's Amazing Statistics Program) application. The population of this study are investors who are members of a securities company in Bengkulu Province. The sample selection used purposive sampling method. The results of the analysis of the forming factors of millennial investors in stock transactions are determined by the 4 factors that shape them from the 25 indicators used. Factor one, with its constituent indicators there are 9 factors out of 25 indicators used. Factor two, from the results of the second factor research was formed by 9 indicators of the 25 indicators used. Factor three is formed from 4 indicators, with indicators that form it. Factor four, there are 6 indicators that form from 25 indicators. The four factors formed show rational factors, irrational factors, psychological factors as well as religious factors which determine millennial investors in stock transactions on the capital market. The factors that become investors' preferences in choosing shares are not only rational, irrational and also psychological factors, but religiosity factors are also taken into consideration in decision making and this is a consideration for issuers in their annual reports to be able to reveal their religiosity values.